Proposal of a PCM Underfloor Heating System Using a Web Construction Method - Sanghoon Baek; Jin Chul Park (International Journal of Polymer Science)
Apartment buildings in Korea have adopted underfloor heating systems using web construction methods based on concrete and hot water systems. However, since such systems consume significant amounts of energy for heating owing to their low thermal storage performance, it is necessary to develop a new system that can minimize energy consumption by improving concrete thermal storage performance. This study proposes a phase-change material (PCM) underfloor heating system to reduce energy consumption in apartment buildings. An optimal design for a PCM underfloor heating system is proposed, and thermal storage performance of the proposed system is evaluated experimentally. The temperature range of the PCM for underfloor heating is also calculated considering the proposed design and comfortable heating conditions for domestic apartment buildings. Results indicate that a PCM underfloor heating system can be constructed in the following order: (1) a 210 mm concrete slab, (2) a 20 mm cushioning material, (3) 40 mm of mortar including a 10 mm PCM thermal storage container, and (4) 40 mm of finishing mortar including wire mesh and hot water pipes. The temperature range of the PCM used for underfloor heating in domestic apartment buildings is 32–45°C. Experimental tests reveal that thermal storage performance of underfloor heating systems that apply 35, 37, 41, and 44°C as representative PCM temperatures is superior to existing systems.